The Effect of Cash Turnover and Current Ratio on Return On Asset at PT Pyridam Farma Tbk Period 2010-2022 - Choiril Anam, Akhmad (Yayasan Pendidikan Penelitian Pengabdian Al-amsi, 2024)
This study aims to determine the effect of Cash Turnover and Current Ratio simultaneously on Return On assets in Pt Pyridam Farma Tbk for the 2010-2022 period. This type of research is associative with a quantitative approach. The methods used are descriptive statistical tests, classical assumption tests, and hypothesis tests. The Cash Turnover study results showed no partial effect on Return On Asset with a calculated value of -0.596< a t-table value of 2.2009, a t-test value of 0.563 > 0.05. The results of the Current Ratio study also have no partial effect on return on assets. This is evidenced by the t-statistic Current Ratio value of 0.687 < ttable value of 2.009 and the significance value of 0.577 > 0.05. From the study results, the effect of Cash Turnover and Current Ratio did not signify on Return On Assets.